2014
DOI: 10.1186/ar4557
|View full text |Cite
|
Sign up to set email alerts
|

Synovial explant inflammatory mediator production corresponds to rheumatoid arthritis imaging hallmarks: a cross-sectional study

Abstract: IntroductionDespite the widespread use of magnetic resonance imaging (MRI) and Doppler ultrasound for the detection of rheumatoid arthritis (RA) disease activity, little is known regarding the association of imaging-detected activity and synovial pathology. The purpose of this study was to compare site-specific release of inflammatory mediators and evaluate the corresponding anatomical sites by examining colour Doppler ultrasound (CDUS) and MRI scans.MethodsRA patients were evaluated on the basis of CDUS and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Worthy of note, synovial production of IL-6 was found to associate with synovitis as detected by MRI and pD [25]. This in accordance with our own results, depicting that IL-6, but not other cytokines, correlated positively with DAS28, swollen joint count, 10-joint pD score and GS/pD of both wrists.…”
Section: Ultrassound Parameters and Synovial Tissuesupporting
confidence: 90%
“…Worthy of note, synovial production of IL-6 was found to associate with synovitis as detected by MRI and pD [25]. This in accordance with our own results, depicting that IL-6, but not other cytokines, correlated positively with DAS28, swollen joint count, 10-joint pD score and GS/pD of both wrists.…”
Section: Ultrassound Parameters and Synovial Tissuesupporting
confidence: 90%
“…Another inflammatory mediator that we measured in this study was macrophage inflammatory protein 1␤ (MIP-1␤), which was shown to be involved in synovitis (25); however, we did not observe an association for MIP-1␤ and DAS (data not shown), which was confirmed by a recent study (21). Serum levels of MIP-1␤ are therefore not useful for monitoring disease activity in RA.…”
Section: Discussionsupporting
confidence: 40%
“…Although it is widely appreciated that myeloid cells are crucial in synovial inflammation and the abundance of synovial macrophages correlates with progression of joint erosion, 11 understanding of the specific role of this cell type in the molecular pathogenesis of arthritic damage has been hindered, at least in part, by macrophage heterogeneity. Data from the Immunological Genome Project reveal that murine macrophages from various organs are transcriptionally diverse, with minimal overlap.…”
Section: Pathological Osteoclastogenesismentioning
confidence: 99%